America and Israel: The Thrill Is Gone. Issue 2 (3rd March 2020) - Simon, Steven
Abstract : In recent years, Israeli policy has come to be seen as increasingly misaligned with the ethical and moral life that most American Jews regard as the core of Jewish meaning.